Variable retention harvesting in Great Lakes mixed-pine forests: emulating a natural model in managed ecosystems - Brian J. Palik; Anthony W. D’Amato (Ecological Processes, 2019)
Abstract Variable retention harvesting (VRH) systems have gained wide use in many different forest types across the globe, but largely have been implemented in forests characterized by severe, infrequent disturbance regimes. There has been less attention given to developing VRH approaches in forests that are characterized as having a mixed-severity disturbance regime that often results in only partial mortality of canopy trees in spatially heterogeneous patterns. One example of such a forest type is red pine (Pinus resinosa Ait.)-dominated ecosystem of the western Great Lakes region of North America. The purpose of this review is to provide a conceptual foundation for developing VRH approaches in red pine ecosystems that are based on a mixed-severity disturbance regime. Our contention is that red pine forests managed following a natural model are more resilient to disturbances and external threats such as climate change. For the red pine ecosystem, VRH application should reflect the often severe, but partial canopy removal from natural disturbance that is characteristic of this ecosystem and that results in more than trivial numbers of surviving overstory trees across a range of spatial configurations in regenerating stands. Retained live trees should span a range of diameters, but favor the larger end of the diameter distribution, as this reflects the likely pattern of survival after natural disturbance and is often a key structural element lacking from managed areas. VRH should be applied in ways that vary the spatial pattern of legacy trees in and among stands, but largely in ways that reflect the pattern of spatially patchy canopy structure, with large openings surrounded by a less disturbed matrix, as occurs with a natural disturbance regime. Legacy trees and deadwood structures should reflect the composition of the pre-disturbance forest, including species in addition to dominant red pine. Finally, retained structures should be viewed as dynamic entities that grow, die, and decay and that need to be documented and accounted for over time. While more organizations are incorporating some form of VRH into policy and practice for red pine-dominated ecosystems, this application is not always based on a comprehensive understanding of the actual natural model of development, which reflects a mixed-severity disturbance regime. Our goal is to review the ecological evidence for this disturbance regime and interpret the structural and compositional outcomes of the disturbance model, so as to advance VRH approaches that better emulate the actual disturbance and development model for this regionally important ecosystem.